챗봇 빌더를 활용한 한국어교육용 챗봇 제작 및 검증 연구 : 학습자 인식 조사를 중심으로 - 정진경; 김한샘 (Foreign Languages Education, 31(3), 2024)
The purpose of this study is to develop a chatbot for Korean language education using Google Dialogflow, aiming to determine its effectiveness as a learning tool and to investigate learners’ perceptions of prototype chatbots. Six Korean language education chatbots were developed for beginner Korean language learners, and 30 beginner learners—15 from Mongolia studying in Korea and 15 from Japan studying abroad—were recruited. These learners practiced Korean conversation with the chatbots for about three weeks, and pre- and post-surveys were conducted. Analysis showed that using the chatbots for conversation practice positively impacted learners’ confidence. However, the chatbots’ overall effectiveness fell short of expectations, as significant results were observed only in confidence among the three investigated areas: interest, confidence, and motivation. Learners were generally satisfied with the chatbots, although Japanese learners rated its effectiveness in improving expressions and comprehension skills low, suggesting a need for further analysis. Both groups found voice chatbots more beneficial, underscoring a significant need for individual speaking practice, especially among Japanese learners. Despite limitations such as the inability to engage in flexible conversations, the study demonstrates the potential of chatbots developed as a learning tool and identifies learners’ perceptions from various perspectives.